Servizio sanitario nazionale e Sars-Cov-2: note critiche sulle politiche di promozione della concorrenza nella sanità (TEST BioLaw Journal - Rivista di BioDiritto, 2021)
The article highlights the impact of the pandemic on the National Health Service. After outlining the central role played by the National Health Service in guaranteeing individual freedoms and for social life, the article criticizes the privatization process of the 1990s. In particular, it highlights how the spirit and mission of public service have profoundly changed, invoking the need for a true reform that leads it back to its original mission.
Keywords: National Health Service; privatization; pandemic; social rights; individual freedoms